Neglected vaginal pessary - Jain, Meenu; Rani, Jyotsna; Sehgal, Alka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Vaginal pessary may be opted for management of uterine prolapse as a safe option, but to avoid complications regular follow-up is a must. We are reporting a case of neglected vaginal pessary in a 72 year old female which got embedded in vaginal mucosa and required excision of vaginal band for its removal.